Analytical solution of a class of coupled second order differential-difference equations - L. Jódar; J. A. Martin Alustiza (International Journal of Mathematics and Mathematical Sciences)
In this paper coupled systems of second order differential-difference equations are considered. By means of the concept of co-solution of certain algebraic equations associated to the problem, an analytical solution of initial value problems for coupled systems of second order differential-difference equations is constructed.